Estudo sobre insetos transmissores de doenças na área urbana por meio de uma sequência didática investigativa - Alves, Gernecilene Ferreira (2022)
The motivation is something that should be present in everyone's life, and it could not be different in the student's life and it is up to the teacher to offer a new way of teaching so that the student is motivated to learn, in this sense this research brought through an investigative proposal, to put the student as the center of learning and awaken in this, the motivation for it. The general objective of this work was to "evaluate the application of an investigative and contextualized Teaching Sequence (DS) about the Disease Carrying Insects in Urban Areas in high school students". It was developed with students of the 2nd grade of high school at the Escola Estadual de Ensino Fundamental e Médio Augusto dos Anjos, in the city of Mari-PB. It is a qualitative-quantitative research, with an exploratory approach. The SD was organized in seven stages that included: 1- Survey of previous knowledge; 2- Application of the pre-test questionnaire; 3- Search for information; 4- Expositive and dialogued class; 5- Field class; 6- Knowledge sharing; 7- Post-test application. First, a pre-test questionnaire was applied to probe the students' previous knowledge. Next, there were expository classes and dialogues with the objective of systematizing the knowledge and solving existing doubts through guiding questions. It was proposed that the students do field research in their own homes, gardens, backyards, for possible observations of insect breeding sites and the relationship between garbage and diseases. From there, the students formed research groups to deepen the theme and then to present the results of the research, which was done through Google Meet (note that the whole process occurred remotely due to the COVID-19 pandemic) with the use of Power Point. The PADLET tool was also used, in which the students were able to answer questions about the theme. At the end another questionnaire (post-test) was carried out, in order to analyze the efficiency in the application of the didactic sequence and in the appropriation of the proposed knowledge. Activities were carried out individually and in groups. The results obtained were satisfactory, analyzing the pre-test and the post-test it can be seen that there was significant learning in several questions, although the question about the prevention of diseases caused by Aedes aegypti should be further explored. In all stages we tried to stimulate the participation of students, insert different methodologies, discover the investigative and protagonist side of these students. It was noticed that the use of differentiated methodologies favors learning, investigation, and the student's protagonism. It was possible to observe a greater motivation on the part of the students during the application of the SD. As a final product, a SD manual was organized with all the steps and suggestions for the use of different methodologies so that it can serve as a didactic resource model for other teachers to guide themselves in order to generate a more effective and enjoyable learning experience for their students.